2019
DOI: 10.1101/592980
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

UBR5 is a Novel E3 Ubiquitin Ligase involved in Skeletal Muscle Hypertrophy and Recovery from Atrophy

Abstract: We aimed to investigate a novel and uncharacterised E3 ubiquitin ligase in skeletal muscle atrophy, recovery from atrophy/injury, anabolism and hypertrophy. We demonstrated an alternate gene expression profile for UBR5 versus well characterised E3-ligases, MuRF1/MAFbx, where after atrophy evoked by continuous-low-frequency electrical-stimulation in rats, MuRF1/MAFbx were both elevated yet UBR5 was unchanged. Furthermore, after recovery of muscle mass post tetrodotoxin (TTX) induced-atrophy in rats, UBR5 was hy… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Thus, as noted for all models described in this Section, some caution is warranted when interpreting aspects of mechanistic regulation from these models and extrapolating to human exercise contexts. One notable development has been the development of models of electrical stimulation that are more episodic in nature, and can be applied to deliver low frequency continuous or higher frequency intermittent stimulation to mimic various types of exercise (76,344,345,603).…”
Section: Models Of Increased Contractile Activity That Do Not Mimic H...mentioning
confidence: 99%
“…Thus, as noted for all models described in this Section, some caution is warranted when interpreting aspects of mechanistic regulation from these models and extrapolating to human exercise contexts. One notable development has been the development of models of electrical stimulation that are more episodic in nature, and can be applied to deliver low frequency continuous or higher frequency intermittent stimulation to mimic various types of exercise (76,344,345,603).…”
Section: Models Of Increased Contractile Activity That Do Not Mimic H...mentioning
confidence: 99%
“…Despite marginal non-MyoF proteome alterations in MA participants with training, there were interesting targets that were altered. For instance, the UBR7 E3 ligase was upregulated, and recent evidence suggests that an E3 ligase in this same protein family (UBR5) is required for load-induced skeletal muscle hypertrophy (53). Additionally, the knockdown of another member of this family (UBR4) promotes hypertrophy in Drosophila and mice (54).…”
Section: Proteolysis Targets Manually Interrogated In Both Fractionsmentioning
confidence: 99%
“…Indeed, there seems to be a trend that a larger proportion of the genes that demonstrate hypomethylation are associated with a 'gene turn on' profile in SkM in response to resistance/strength (16,19), high-intensity (15) and aerobic exercise (18,23,24). Importantly, DNA methylome studies have identified novel exercise-responsive genes in human SkM that have not been previously highlighted in mRNA/transcriptome studies (14,25,26). Finally, DNA methylation in SkM also seems to be sensitive to high fat dietary interventions after resistance exercise (27).…”
Section: Introductionmentioning
confidence: 99%
“…19.524676 doi: bioRxiv preprint (16,19), high-intensity (15) and aerobic exercise (18,23,24). Importantly, DNA methylome studies have identified novel exercise-responsive genes in human SkM that have not been previously highlighted in mRNA/transcriptome studies (14,25,26). Finally, DNA methylation in SkM also seems to be sensitive to high fat dietary interventions after resistance exercise (27).…”
Section: Introductionmentioning
confidence: 99%